ANALISIS HUBUNGAN FAKTOR FAKTOR YANG MEMPENGARUHI PREDIKAT PERUSAHAAN ASURANSI UMUM DI INDONESIA PERIODE DESEMBER 2013 – NOVEMBER 2014 - Tri Retnaning Nur Amanah; Tatik Widiharih; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Human life often faces an uncertain situation and risks. In reducing uncertainty, human can protect themselves by choosing an insurance company. One that can be considered in the selection of protection is to observe the predicate of the insurance company. Predicate of general insurance company in Indonesia period December 2013 to November 2014, issued by the research institute Info bank categorized into 4 (four), there are very good, good, good enough and not good. Rating of predicate using factors commonly used to observe the financial performance. Those factors are the Risk Based Capital, the growth of gross premium income, the load (claims, efforts, and commissions) to net premium income, the net income (loss) before taxes compared to averages of equity, the net income (loss) comprehensive compared with the average of equity capital, the liquidity, sufficiency investments and current assets to total assets, the growth of their own capital, their own premium retention on their own capital, the underwriting results compared with net premium, the balance on investment with net premium income, investment of current assets to total assets. This study aims to determine the factors that are supposed to influence the predicate of insurance using ordinal logistic regression. Results of the analysis showed that the growth in gross premium income and load (claims, efforts, and commissions) to net premium income have significant effect (α = 5%) to predicate of insurance.Keywords: ordinal logistic, gross premium, the load to net premium, predicate of insurance.